Community Development dalam Penerapan Nilai-Nilai Moral Kristiani di SMAK Setia Bakti Ruteng, Kabupaten Manggarai - Keristian Dahurandi; Paulus Tolo; Fredrikus Djelahu Maigahoaku (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2022)
Character building is an accentuation of Indonesian educational project today. The mandate of the Preamble of the 1945 Constitution in the fourth paragraph indicates the goal of education that is to educate the nation's life. The mandate is operationally implemented in the strategic plan of formal education through the “2013 Curriculum” design which emphasizes